2017
DOI: 10.1111/tbed.12597
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Leishmania spp. in Bats from an Area of Brazil Endemic for Visceral Leishmaniasis

Abstract: The multihost parasites Leishmania spp. infect a broad range of wild mammalian species including bats. Several species of bats have adapted to a variety of food resources and shelters in urban areas. This study aimed to detect Leishmania spp. DNA in bats present in forest fragments located in metropolitan areas endemic for leishmaniasis in Campo Grande, Mato Grosso do Sul (MS), Brazil. Blood samples were obtained from 80 individuals, including eight species of Phyllostomidae and one species of Vespertilionidae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 40 publications
1
15
0
1
Order By: Relevance
“…We observed 8·0% of positive samples for Leishmania infection. Diverse studies have reported natural infection of Leishmania in bats suggesting a relevant epidemiological role in the transmission cycle of leishmaniasis (Rotureau et al 2006; Savani et al 2010; Shapiro et al 2013; Millan et al 2014 b ; Berzunza-Cruz et al 2015; de Rezende et al 2017). Also, the fact of finding Leishmania infection in a geographical region that is not considered endemic for leishmaniasis shows the relevant role that bats play for the dispersal of distinct pathogens as Leishmania .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed 8·0% of positive samples for Leishmania infection. Diverse studies have reported natural infection of Leishmania in bats suggesting a relevant epidemiological role in the transmission cycle of leishmaniasis (Rotureau et al 2006; Savani et al 2010; Shapiro et al 2013; Millan et al 2014 b ; Berzunza-Cruz et al 2015; de Rezende et al 2017). Also, the fact of finding Leishmania infection in a geographical region that is not considered endemic for leishmaniasis shows the relevant role that bats play for the dispersal of distinct pathogens as Leishmania .…”
Section: Discussionmentioning
confidence: 99%
“…2010; de Rezende et al . 2017). Herein, we detected single infections of L. infantum , L. amazonensis and L. braziliensis , which highlights the epidemiological threat in the transmission to humans causing visceral, cutaneous and/or mucocutaneous leishmaniasis (Lemos and Lima 2005; Paula et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR has been used to explore the presence of Leishmania DNA in tissues of wild mammals both in New World and Old World, to find potential parasite reservoirs. For example, Leishmania DNA was found from rodent and bat spleen tissues [ 52 55 ]. Furthermore, L. infantum DNA has been also retrieved from hair of wild mammals, such as Leporidae [ 56 ], fox, wolf, rat, marten and hedgehog [ 57 ].…”
Section: Clinical Samplesmentioning
confidence: 99%
“…About 70 species of mammals, including humans, are considered vertebrate hosts of different species of Leishmania around the world, and some of them are reservoirs of the parasite in nature [ 1 ]. Although the natural infection in rodents [ 3 , 4 ] and canids [ 5 10 ] is more common, the parasite is able to infect xenarthrans [ 11 , 12 ], hyraxes [ 13 ], marsupials [ 14 ], chiropterans [ 15 17 ], lagomorphs [ 18 21 ], procyonids [ 11 , 22 ], felids [ 23 26 ], Perissodactyla [ 27 , 28 ], and primates [ 11 , 29 ]. Determining the precise role played by each host in the transmission cycle remains a challenge.…”
Section: Introductionmentioning
confidence: 99%